Synthesis and characterization of a new two photon excitable acid sphingomyelinase FRET probe - Mohamed, Zain H.; Rhein, Cosima; Schmid, Benjamin; Tripal, Philipp; Kornhuber, Johannes; Arenz, Christoph (Bioorganic & medicinal chemistry, 2021)
Recently, FRET probes for acid sphingomyelinase (ASM) have enabled the observation of enzyme activity in intact cells for the first time. Here we present an ASM FRET probe specifically optimized for 2-photon excitation. To facilitate probe characterization and comparison to the previous probe, we mixed the two intact probes with defined amounts of the probes' ceramide cleavage products and mounted them on lipid beads. Directly excited NBD FRET acceptor fluorescene proved to be a useful means of reference and showed that the new probe is brighter, albeit only moderately, than the previous one. The new probe was then used to detect inhibition by various ASM inhibitors microscopically for the first time. Also in cells, directly excited acceptor fluorescence proved to be a useful parameter in addition to FRET to visualize inhibition of ASM.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antidepressants; Enzyme inhibitors; FRET probes; Förster resonance energy transfer (FRET); Sphingolipids; Two-photon microscopy